Meaningful Work, Post-Work, and Contemporary Aristotelianism - Egidijus Mardosas (Problemos)
The paper explores the relation between a contemporary Aristotelian conception of human flourishing and two critical perspectives on work. The meaningful work perspective inquires what kind of work would be meaningful, by arguing that meaningful work is essential for human flourishing. The post-work perspective argues that good life lies outside work and workplaces and calls to eliminate work as much as possible. The paper suggests that it is possible to acknowledge the insights of both perspectives via contemporary Aristotelian notions of practice and human flourishing. The notion of practice incorporates the conception of meaningful work, yet it applies to nonwork activities as well. Conceptualization of human well-being via the notion of practice also responds to the post-work challenge of conceiving human flourishing without prioritizing work over other meaningful activities. In this way, a contemporary Aristotelian conception of human flourishing supports both the need for better work and less work.